Concentration in the Banking Sector and Financial Stability : New Evidence - Calice, Pietro (World Bank, Washington, DC, 2018)
Theory suggests that the effect of banking market concentration on financial stability is mediated by several competing variables. Using a sample of 68 countries from 1997 to 2015, this paper proposes a unified empirical framework to test for the simultaneous presence and impact of the mediators through which concentration is expected to impact financial stability. The results indicate that the magnitude and net effect of the mediators depend upon the level of concentration. At lower levels of concentration, increasing concentration improves banking system stability via profitability. At higher levels of concentration, increasing concentration makes the banking system more fragile because of the cost of credit, diversification and the ease of monitoring. For intermediate levels, concentration has no significant effect on financial stability, as the competing moderators cancel each other out. The results suggest that an intermediate level of concentration may be optimal for welfare.